Integrated rural development - Khan, Ali Akhtar (1977)
This paper contends that integrated rural development (IRD) provides a basis for improving the quality of rural life. The IRD approach is concerned with both production increases and the equitable distribution of benefits from these increases. In analyzing the common conceptual and operational problems confronting the integrated approach, a solution that may lead to its success is suggested: an IRD methodology which includes the formulation of objectives and development goals, adoption of strategies and mobilization of resources to achieve these goals, leadership and institution building, and reliance on research and
training. The experiences of Taiwan, Bangladesh, Sri Lanka, and the Philippines are used as case illustrations.
Keywords: Rural development; Rural development -- Case studies; Rural development -- Southeast Asia; Rural development projects -- Demographic aspects